Aerogel de celulose bacteriana silanizada incorporado de óleos naturais como potencial curativo dérmico - Pontes, Evellheyn Rebouças (2020)
The versatility and biocompatibility of bacterial cellulose (BC) allows its use in biomedical applications, such as in the treatment of skin lesions. BC has important characteristics for a dressing, but has no antimicrobial capacity, requiring the addition of pharmacological agents. An alternative is the incorporation of natural oils, such as copaíba essential oil (OEC), geranium essential oil (OEG) and buriti vegetable oil (OVB), which have antibacterial effect, analgesic and anti-inflammatory properties. However, the hydrophilicity characteristic of BC makes it impossible to incorporate these oils, being an alternative to chemical modification of the BC suspension by silanization using methyltrimethoxysilane (MTMS), obtaining a hydrophobic matrix. In this work, BC membranes were deconstructed, added with carboxymethylcellulose (CMC) and defibrillated in a colloid mill to obtain the BC suspension. The suspension was hydrophobized and lyophilized to obtain the hydrophobic airgel. The modified BC airgel showed a high degree of hydrophobization with a contact angle of 127.9 ° with water. This modification can also be proved by the FTIR analysis in which it was possible to observe the vibration bands at 780 cm-1, 905 cm-1, and 1275 cm-1 regarding the connections made between the silicon derived from the MTMS reagent with the methyl group (-CH-3), carbon and oxygen in the cellulosic chain. The silanized airgel was able to absorb 1.76 times more oil than the standard BC airgel. The cytotoxicity tests demonstrated that the silanized airgel was not toxic to fibroblast cells (L929) and keratinocytes (HaCat), allowing cell viability of 85% and 95% after 48 hours, respectively. The GC-EM analyzes of the oils showed that the major constituents of the OEC are sesquiterpenes (77%), while that of OEG are monoterpenes (48%), and OVB are fatty acids (86%). Regarding antimicrobial activity, only OEG showed bactericidal action for E. coli and S. aureus at a concentration of 16 mg.mL-1 and fungicidal action for C. albicans at a concentration of 4 mg.mL-1. In the cytotoxicity analysis, the OVB presented the best results of cell viability for both strains. After 48 hours of cell culture, the concentration of 100 µg.mL-1 allowed the viability of approximately 142% and 174% of fibroblast cells (L929) and keratinocytes (HaCat), respectively. Thus, the results obtained in this work make promising the use of silanized BC airgel incorporated with oils for the treatment of wounds.